DRIVING FACTORS OF IMPULSIVE BUYING DECISIONS: THE CASE OF BUY NOW PAY LATER SERVICE - Wiyata, Wiyata; Datu Arya Kusuma (LPSDI Bina Patria, 2024)
This paper investigates the driving factors behind impulsive buying decisions in the context of Buy Now Pay Later (BNPL) services. Impulse buying is a common behavior characterized by spontaneous purchases without prior planning. With the rise of BNPL services offering convenient payment options, understanding the determinants of impulsive buying within this framework is crucial. Drawing on consumer behavior theories and empirical research, this study examines key factors influencing impulsive buying decisions in the case of BNPL. Factors such as installment payment, conspicuous consumption, critical mass, and price discount are explored. To test our research model and hypotheses, we conducted a questionnaire survey and used structural equation modeling based on data collected from 120 respondents in Indonesia. Results from the empirical investigation show that consumer lifestyle affects consumer adoption of new ICT products, partially through the value preferences they form towards new ICT products along various product attributes, including functional, symbolic, and cost attributes.